Enhancement of colour quality, growth, and health status of rainbow Kurumoi fish Melanotaenia parva through dietary synthetic carotenoids supplementation - Nina Meilisza; Muhammad Agus Suprayudi; Dedi Jusadi; Muhammad Zairin Junior; I Made Artika; Nur Bambang Priyo Utomo (Jurnal Akuakultur Indonesia)
ABSTRACT